Canine Heartworm Disease in Nueva Ecija, Philippines: A Clinic-Based Epidemiological Study - Nicole C. Agunday; Christian C. Santos; Armando G. Agustin (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
This study profiled canine heartworm disease (CHD) cases recorded from 2020 to 2022 in veterinary clinics across Cabanatuan, Gapan, Muñoz, and San Jose, Nueva Ecija. Data from eight clinics included age, sex, breed, preventive history, and clinical signs. A total of 378 confirmed CHD cases were identified using rapid antigen tests. Most infections occurred in dogs aged over 13 months (63.85%), with slightly higher prevalence in males (54.35%) and toy breeds (62.27%). Notably, 90.77% of affected dogs had no record of heartworm prophylaxis. Coughing (86.28%) was the most frequent clinical sign. Cases peaked during the rainy season (June–November), with Cabanatuan City recording the highest number (n = 304). Statistical analysis indicated a significant correlation between CHD and age. These findings highlight the importance of year-round preventive care and increased owner awareness, particularly in high-risk areas.